An assessment on the use of stationary vehicles to support cooperative positioning systems1. Issue 3 (4th March 2018) - Ordóñez-Hurtado, Rodrigo H.; Crisostomi, Emanuele; Shorten, Robert N.
ABSTRACT: In this paper, we evaluate the ability of stationary vehicles (e.g. parked or temporary stopped cars) as tools to enhance the capabilities of existing cooperative positioning algorithms in vehicular networks. First, some real-world facts are provided to support the feasibility of our ideas. Then, we examine the idea in greater details in terms of the technical requirements and methodological analysis, and provide a comprehensive experimental evaluation using dedicated simulations. The routing of a drone through an urban scenario is presented as a non-traditional application case, where the benefits of the proposed approach are reflected in a better utilisation of the flight time.